2021
DOI: 10.3389/fonc.2021.780601
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Three Autophagy-Related Long Noncoding RNAs as Prognostic Signature in Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is featured by common occurrence and poor prognosis. Autophagy is a biological process that has been extensively involved in the progression of tumors. Long noncoding RNAs (lncRNAs) have been discovered to be critical in diagnosing and predicting various tumors. It may be valuable to elaborate autophagy-related lncRNAs (ARlncRNAs) in CCA, and indeed, there are still few studies concerning the role of ARlncRNAs in CCA. Here, a prognostic ARlncRNA signature was constructed to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Cells were incubated overnight in a CO 2 incubator at 37 ℃. The control group and experimental group with different concentrations of DMDD (5,10,20,40, and 80 μM/L) were set up and incubated for 24, 48, and 72 h. Then, 10 μL CCK8 solution was added and incubation was continued for 2 h. The absorbance value of each well was read at 450 nm on an enzyme standard instrument. Cell viability (%) = [optical density (OD) of experimental group − OD of control group]/(OD of control group − OD of blank group) × 100%, and the halfinhibitory concentration (IC50) of DMDD on QBC939 cells was calculated.…”
Section: Cck8 Assay For Qbc939 Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were incubated overnight in a CO 2 incubator at 37 ℃. The control group and experimental group with different concentrations of DMDD (5,10,20,40, and 80 μM/L) were set up and incubated for 24, 48, and 72 h. Then, 10 μL CCK8 solution was added and incubation was continued for 2 h. The absorbance value of each well was read at 450 nm on an enzyme standard instrument. Cell viability (%) = [optical density (OD) of experimental group − OD of control group]/(OD of control group − OD of blank group) × 100%, and the halfinhibitory concentration (IC50) of DMDD on QBC939 cells was calculated.…”
Section: Cck8 Assay For Qbc939 Cell Viabilitymentioning
confidence: 99%
“…Studies have reported that impaired autophagy regulation is closely associated with carcinogenesis, metastasis and poor prognosis of bile duct cells and can be an effective anticancer target. Three autophagy-associated long-stranded non-coding RNAs have been identified as prognostic features of bile duct cancer (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…They function as a double‐edged sword in carcinogenesis and metastasis. For example, autophagy works as a tumor‐suppressive process that avoids persistent tissue damage and cell injury, particularly during the early stages of carcinogenesis 8 . Numerous types of cancer, including HCC, strongly correlate with inflammation and tumor growth and have an unfavorable prognosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, autophagy works as a tumor-suppressive process that avoids persistent tissue damage and cell injury, particularly during the early stages of carcinogenesis. 8 Numerous types of cancer, including HCC, strongly correlate with inflammation and tumor growth and have an unfavorable prognosis. 9 Previous studies have proven that inhibiting autophagy increases the inflammatory response, hence boosting the growth of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al determined the prognostic signature based on autophagy-related lncRNAs (ATRlncRNAs); this signature might potentially be used for targeted therapy and evaluation of the prognosis of colon cancer patients [ 17 , 18 ]. Liu et al investigated the clinical role of ATRlncRNAs in cholangiocarcinoma and demonstrated its potential for the personalization of cholangiocarcinoma treatment [ 19 ]. Deng et al proposed a six-ATRlncRNA signature that might be helpful for individualized therapy and PC patient assessment.…”
Section: Introductionmentioning
confidence: 99%